Spatiotemporal features of the soil moisture across Northwest China using remote sensing data, reanalysis data, and global hydrological model - Wang, Meijun; Yin, Gang; Mao, Min; Zhang, Hao; Zhang, Hua; Hu, Zengyun; Chen, Xi (Frontiers in Environmental Science, 2023)
Soil moisture is an important factor affecting the change of land surface hydrological processes and affect the distribution of material and energy exchanges between the land and atmosphere and vegetation's temporal and spatial distributions, especially in arid and semi-arid regions. This paper focuses on soil moisture features across Northwest China, the core region of the Silk Road Economic Belt. Six soil moisture datasets from the period 1981-2020 were employed, which included ERA5 (the European Centre for Medium-Range Weather Forecasts Atmospheric Reanalysis 5), ESA-CCI (European Space Agency Climate Change Initiative), GLDAS (Global Land Data Assimilation System), MERRA-2 (The Modern-Era Retrospective Analysis for Research and Applications, Version 2), RSSSM (A Remote Sensing-based global 10-day resolution Surface Soil Moisture dataset), and SSM-Feng (Regional multimodal fusion of surface soil moisture data in China). The temporal and spatial variation of the linear trend and abrupt change characteristics at seasonal and annual scale were explored. The results are as follows: (1) ESA-CCI, GLDAS, and MERRA-2 have a slow increase in annual soil moisture tendency with a rate of less than 0.001 m3/m3/year, while ERA5 and SSM-Feng have a significant decreasing linear trend at a rate of 1.31×10-4 m3/m3/year and 1.01×10-4 m3/m3/year (p < 0.05). (2) In autumn and winter, only GLDAS and MERRA-2 showed significant increasing trends. In the growing season (i.e., from April to October), the soil moisture of ESA-CCI, GLDAS, and MERRA-2 significantly increased at the rates of 3.29×10-4 m3/m3/year, 3.30×10-4 m3/m3/year and 6.64×10-4 m3/m3/year (p < 0.05). (3) ERA5 and ESA-CCI have frequent abrupt changes in 1984, 1987, and 2006 for ERA5, 2010–2012, and 2019–2020 for ESA-CCI. (4) In terms of spatial variations, most datasets show soil moisture have increased across most regions. The ERA5, ESA-CCI, GLDAS, MERRA-2, and SSM-Feng datasets show decreased soil moisture in the Tarim Basin. The conclusions of this study deepen the understanding of temporal and spatial variation in soil moisture in arid areas of Northwest China. Through these conclusions, a certain theoretical basis can be provided for the complex water cycle process in the arid region.